Potential associations of adult nocturia. Results from a national prevalence study. Issue 3 (7th February 2021) - Azuero, Julian; Santander, Jessica; Trujillo, Carlos Gustavo; Caicedo, Juan Ignacio; Zuluaga, Laura; Becerra, Ana María; Daza, Fabián; Rondón, Martin; Plata, Mauricio
Abstract: Aim: To determine the prevalence of nocturia and associated risk factors in the Colombian population aged ≥18 years old. Methods: This is a cross‐sectional population‐based study conducted in 1060 participants in Colombia. Nocturia was assessed with the Spanish version of the ICIQ‐OAB, using the ICS terminology. Descriptive statistics were used to evaluate nocturia prevalence. Logistic regression analysis was carried out to determine the association of nocturia with predefined variables. Results: The prevalence of nocturia was 55.9% and it was more common in women than men (53.96% vs. 46.04%; p  = .004). At least three episodes of nocturia were observed in 20.37% of the participants who had a severe alteration in their quality of life ( p  < .01). The bivariate model showed an association between nocturia and obesity (odds ratio [OR], 1.69; 90% confidence interval [CI]: 1.22–2.34), diabetes mellitus (OR, 2.99; 90% CI: 1.86–4.83), high blood pressure (OR, 2.04; 90% CI: 1.52–2.72), cardiovascular disease (OR, 1.75; 90% CI: 1.08 – 2.83), depression (OR, 1.89; 90% CI: 1.23–2.89), obstructive sleep apnea (OR, 1.70; 90% CI: 1.17 ‐ 2.46), and childhood enuresis (OR, 1.45; 90% CI: 1.04–2.02). The multivariate model showed an association with obesity (OR, 2.0; 95% CI: 1.14 ‐ 3.51) in women, as well as age ≥ 65 years (OR, 3.18; 95% CI: 1.26 – 8.02) and erectile dysfunction (OR, 3.44; 95% CI: 1.21 – 9.72) in men. Childhood enuresis was significantly associated with nocturia in both genders (OR, 1.61; 95% CI: 1.09 ‐ 2.40 in women and OR, 1.66; 95% CI: 1.09–2.52 in men). Conclusion: There is a significant prevalence of nocturia in our population and a clear association with impaired quality of life. We consider important to inquire about history of childhood enuresis to define the risk of presenting nocturia in adulthood. Nocturia was associated with multiple comorbidities. Obesity and erectile dysfunction play an important role as modifiable risk factor.